Seasonal variation among tuberculosis suspects in four countries - Mabaera, Biggie; Naranbat, Nymadawa; Katamba, Achilles; Laticevschi, Dumitru; Lauritsen, Jens M.; Rieder, Hans L. (International Health, 2009)
The objective of the study was to analyze monthly trends across a calendar year in tuberculosis suspects and sputum smear-positive cases based on nationally representative samples of tuberculosis laboratory registers from Moldova, Mongolia, Uganda and Zimbabwe. Out of the 47 140 suspects registered in the tuberculosis laboratory registers, 13.4% (6312) were cases. The proportion varied from country to country, Moldova having the lowest (9%) and Uganda the highest (21%). From the monthly proportion of suspects and cases among total suspects and cases, seasonal variations were most marked in Mongolia which, among the four countries, also has the most pronounced seasonal variation in ambient temperature. Female suspects were consistently older than female cases in all four countries. Among males, male suspects were almost consistently older than male cases, most consistently in Moldova. Seasons seem to affect attendance to diagnostic laboratory services, evidenced by the contrasting findings of Mongolia (extreme continental northern climate) compared to Uganda (equatorial climate). A combination of external and possibly endogenous factors seems to determine whether tuberculosis suspects and cases present themselves to health care facilities.
Keywords: Tuberculosis; Laboratory; Seasonal variation; Trends